2017
DOI: 10.1111/imb.12325
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of a metathoracic scent gland desaturase enhances the production of (E)‐4‐oxo‐2‐hexenal and suppresses female sexual attractiveness in the plant bug Adelphocoris suturalis

Abstract: Insect sex pheromones (SPs) are central to mate-finding behaviour, and play an essential role in the survival and reproduction of organisms. Understanding the roles, biosynthetic pathways and evolution of insect chemical communication systems has been an exciting challenge for biologists. Compared with Lepidoptera, little is known about the mechanisms underlying pheromone biosynthesis in Hemiptera. In this study, we isolated and characterized two new desaturase-like genes, termed Asutdes1 and Asutdes2, from Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…For instance, desaturases Δ5, Δ9 and Δ12 in the flour beetle Tribilium castaneum (Coleoptera) [32,33] and Δ9 desaturase in the house cricket Acheta domesticus (Orthoptera) [34] have been cloned and functionally characterized. In contrast, we face a shortage of information about the desaturases of Hemipteran insects, although recently a metathoracic scent gland desaturase has been found that is involved in female sexual attractiveness in the plant bug Adelphocoris suturalis [35].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, desaturases Δ5, Δ9 and Δ12 in the flour beetle Tribilium castaneum (Coleoptera) [32,33] and Δ9 desaturase in the house cricket Acheta domesticus (Orthoptera) [34] have been cloned and functionally characterized. In contrast, we face a shortage of information about the desaturases of Hemipteran insects, although recently a metathoracic scent gland desaturase has been found that is involved in female sexual attractiveness in the plant bug Adelphocoris suturalis [35].…”
Section: Introductionmentioning
confidence: 99%
“…Adelphocoris suturalis nymphs were obtained from Huazhong Agricultural University and reared with fresh mung bean seedlings and pea aphids (Acyrthosiphon pisum) in clean plastic containers at 25 ± 2 • C, 70 ± 5% relative humidity, under the photoperiod of 16 h light/8 h dark (Luo et al, 2017a). E. cloacae (strain no.1.2022) was obtained from China General Microbiological Culture Collection Center and was cultured in LB (Luria-Bertani) medium at 37 • C. B. bassiana isolate 093 was cultured on Potato Dextrose Agar (PDA) medium at 25 • C. As a dispersing agent, 0.05% (v/v) Tween 80 solution was used to collect the fungal conidia.…”
Section: Insect Rearing and Pathogenic Infection Bioassaysmentioning
confidence: 99%
“…Biological control methods including transgenic plants, entomopathogenic microbes, or the combination of both, showed promising efficacy in pest's management (Yajuan and Wu, 2010;Luo et al, 2017b). Many studies have focused on A. suturalis ecology and physiology Zhang et al, 2011;Feng et al, 2012;Luo et al, 2017a),reporting its transcriptomes at different developmental stages and pheromone biosynthesisrelated genes (Luo et al, 2014;Tian et al, 2015). Together these reports identified candidate genes for further transgenic plants development.…”
Section: Introductionmentioning
confidence: 99%
“…Odorant binding proteins play a role in the identification of volatile compounds and sex pheromones [98] Lygus lineolaris Polygalacturonase gene mainly express in salivary gland demonstrating that PGs are salivary enzyme [99] Lygus hesperus Knight Cardinal gene is essential for eye colouration [100] Adelphocoris suturalis Desaturase-like genes, role in sex pheromones biosynthetic pathway [101] RNAi in immunity-related genes…”
Section: Adelphocoris Lineolatusmentioning
confidence: 99%